Variation in the grass pea (Lathyrus Sativus L.) and wild species - Jackson, M. T.; Yunus, A. G. (Springer, 1984)
Forty-nine accessions of Lathyrus sativus were studied for morphological variation. Data were analysed using Principal Components Analysis and Cluster Analysis . The variation in 14 species of Section Lathyrus was also evaluated in order to ascertain affinities between L. sativus and other species. L. sativus is a highly variable species, and there is a clear distinction between the blue-flowered forms from south-west Asia, Ethiopia and the Indian subcontinent, and the white and white and blue flowered forms with white seeds which have a more westerly distribution. Differences in vegetative parts may be due to selection for forage types. L. sativus appears to be closely related to L. cicera and L. gorgoni, and this relationship needs further investigation